The Artist and His Oeuvre in G. K. Chesterton’s Biography: G. F. Watts - Ayupova, Kamilya F.; Kozyreva, Maria A.; Akimova, Tatyana I. (Journal of History Culture and Art Research, 2017)
The article offers a close analysis G. K. Chesterton’s largely overlooked biographical essay G. F. Watts (1904). The authors study the genre specifics of the biography of an artist, as well as the problems of biographical theory. In G. F. Watts, which the authors define as the literary portrait of the artist, Chesterton traces his subject’s personality through his art. He views Watts’ creativity through his Victorianism. Analyzing the artist’s oeuvre Chesterton also reveals his own artistic methods, which he would later use in his novels. Being the critic’s early work, the book allows a closer view of the shaping of his philosophical ideas and artistic principles, which would take form in his later writings. The authors come to the conclusion that, for all its undeniable merits, the biography in a whole is rather subjective, and hence, its value lies in Chesterton’s general insights on fine art.